Bagaimana Peran Orangtua Mempengaruhi Pilihan Karir Mahasiswa? dari Perpektif Roe's Personality Theory: A Systematic Literature Review - Cusnia, Azahra; Afdal, Afdal; Hariko, Rezki; Nurfarhanah, Nurfarhanah (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2024)
Career choice is one of the most important decisions in a student's life. This article is a systematic literature review that aims to analyse the role of parents in influencing college students' career choices from the perspective of Roe's personality theory. It collects and analyses relevant research in this area to gain a comprehensive understanding of the relationship between parental roles and college students' career choices.The results of this literature review indicate that parents have a significant role in influencing college students' career choices. In addition, factors such as gender, parents' educational background, and family structure can also influence parents' influence on students' career choices. However, research also shows that other factors beyond parental influence, such as individual interests, educational experiences, and environmental factors, also have a significant impact on students' career choices. Therefore, it is important to consider other interacting factors in understanding students' career choices holistically.